Maternal uniparental disomy for chromosome 14 in a boy with a normal karyotype. Issue 10 (1st October 1999) - Hordijk, Roel; Wierenga, Henk; Scheffer, Hans; Leegte, Beike; Hofstra, Robert M W; Stolte-Dijkstra, Irene
Abstract : We report on a boy with a maternal uniparental disomy for chromosome 14 (UPD(14)). At 7 years of age he was referred to us by the paediatrician because of symptoms of Prader-Willi syndrome (PWS). He showed short stature, obesity, mild developmental delay, cryptorchidism, and some mild dysmorphic features. The history further indicated intrauterine growth retardation at the end of the pregnancy. His mother was 44 years of age at the time of his birth. After birth he showed hypotonia with poor sucking, for which gavage feeding was needed. Motor development was delayed. After 1 year he became obese despite a normal appetite. Recurrent middle ear infections, a high pain threshold, and a great skill with jigsaw puzzles were reported. There were no behavioural problems or sleep disturbance. Chromosomal analysis was normal (46, XY). DNA analysis for Prader-Willi syndrome showed no abnormalities. Two years later he was re-examined because we thought his features fitted the PWS-like phenotype associated with maternal UPD(14). At that time precocious puberty was evident. DNA analysis showed maternal heterodisomy for chromosome 14. In all the previously described 11 cases with maternal UPD(14), a Robertsonian translocation involving chromosome 14 was detected cytogenetically before DNA analysis. This is the first report of diagnosis of maternal UPD(14) based on clinical features. This finding underlines the importance of DNA analysis for maternal UPD(14) in patients with a similar PWS-like phenotype even without previous identification of a Robertsonian translocation involving chromosome 14.